Villa Emma : ragazzi ebrei in fuga, 1940-1945 - Voigt, Klaus (Biblioteca di storia, 2002)
In 1940, Recha Freier was in Berlin trying to arrange the emigration to Palestine of the families of Jewish men of Polish citizenship whom the Germans had interned. After fleeing in July to Zagreb, she organized the transfer of children from these families to Zagreb in the hope that they could continue on to Palestine. Other children joined; in the end there were some 140. After Freier herself left for Palestine, the children were cared for by youth leaders, led by Josef Indig (now Ithai). Ninety of them obtained certificates and left for Palestine. After Zagreb fell to the Ustasha, Indig fled with the remaining children, first to Slovenia and then to Italy. DELASEM housed them in the Villa Emma, a mansion in Nonantola (near Modena), and named an Italian director who took over many of Indig's functions. More children joined at this time, mostly from Yugoslavia. After the German invasion in 1943, they were hidden by townspeople and in a seminary for priests until they managed to escape to Switzerland. Emphasizes psychosocial aspects of the group